(untitled) (Colombia Medica, 2018)
Introduction: Although the association between diabetes mellitus type 1 (T1DM) and celiac disease (CD) is well established; there are only a few studies that focus on South American children, haplotypes and their possible associations. Objective: To determine the prevalence of CD markers in a group of children with T1DM and to analyze the associated clinical, immunological and genetic manifestations. Methods: A prevalence study focusing on children with T1DM who were assessed based on variables including sociodemographics, anthropometric information, disease characteristics, laboratory results and family medical history. In partitipants a positive tTG2 (Ig A antitransglutaminase), a duodenal biopsy and genotype were performed. The proportion of children with T1DM and CD was estimated (CI 95%). Determinations of central tendency, univariate and bivariate analysis, were also performed; p <0.05 was considered significant. Results: Thirteen (8.4%) of the 155 children (53.6% girls, 11.0 ±3.6 years, 2-18 years) with T1DM were tTG2 positive, four had CD (2.6%), seven had potential CD (4.5%) and nine were HLA DQ2/DQ8 positive (5.8%). Children with T1DM and CD had their last ketoacidotic episode (21.5 ±30.4 months versus 69.5 ±38.8 months, p= 0.0260) earlier than children with T1DM and potential CD. There were no differences with anthropometry or with the laboratory results regarding glycemic control. Conclusions: The prevalence of CD in these children with T1DM is higher than that reported in other South American countries. The prevalence of CD was found to be associated with the time of presentation of T1DM and its main allele, the DQ2/DQ8. These findings are different from what has been described in other places around the world.